Kan̄phatthana rabop sukkhaphāp ʻamphœ̄ thī prachāchon pēn sūnklāng - Suphattrā Sīwanitchākō̜n (Mūnnithi Sathāban Wičhai læ Phatthanā Rabop Sukkhaphāp Chumchon (Mō̜sō̜phō̜chō̜.), 2016)
On development of health care and the community health service system in Thailand.